What Happens in Teachers? Brains when They Think about Working with Students - Szymczak, Joanna (INSTED: Interdisciplinary Studies in Education & Society, 2017)
The article is an attempt to present the reflection models concerning working with students, which were constructed based on the analysis of the data gathered in a research project. I focused on providing the answer to the question of how doing reflection on working with students is documented in the narration of the research participants, i.e. early education teachers. I also tried to reconstruct a specific reflection way, which was created and followed by the interviewees. I tried to consider such aspects as: what triggers reflection?; how does reflection proceed?; what does it lead to?; when does doing reflection end? Moreover, I presented a strategy which was documented in the empirical data, and which the research participants used in order to stimulate their own thinking process, and named it talking for thinking. I emphasised the methodological solutions which were used in the research, i.e. an episodic interview and the grounded theory from the perspective of K. Charmaz. I took account of the following theories which allowed me to build a theoretical framework for thinking about reflection and methodological proceeding: constructivism from the perspective of H. Berner, N. Goodman and K. J. Gergen; the constructivist model of cognition and the non-classical sociology of knowledge from the perspective of A. Zybertowicz, A. Gidden?s structuration theory, H. Blumer and E. Goffman?s symbolic interactionism, phenomenology from the perspective of E. Husserl, P. L. Berger and T. Luckmann, and A. Schütz, J. Burner?s sociocultural approach, J. Dewey?s concept of reflective thinking, J. Kozielecki?s concept of human cognition and E. J. Langer?s notions of mindfulness and mindlessness. In the paper, I made an attempt to create a cultural space for considerations about early education teachers? reflection concerning working with students.